Działania operacyjne SB wobec „Tygodnika Powszechnego” w latach 1957–1965 (wybrane zagadnienia) - Musiał, Filip; Szarek, Jarosław (Pamięć i Sprawiedliwość, 2006)
„Tygodnik Powszechny” – a Catholic socio-cultural magazine issued in Cracow gathered catholic opposition against communist authorities. The policy of so called „mild opposition” accepted by the magazine allowed for publishing a weekly magazine, the programme of which differed from requirements of the state authorities. The magazine was tolerated by the communists, who used the fact of its existence as a proof for the alleged pluralism and democratic rule in Poland. For all the period of its existence, from the first issue in 1945 till until the fall of the communist regime, the communist political police was interested in the editorial staff of the magazine. In 1957–1965 Security Service was leading a group operational action with a code names „Pióro” and later „Pismak” against „leadership active” of the editorial staff. The information was gathered from telephone bugs installed in the editorial office, room bugging (code name „Gawron”) operating since 1963 and personal sources of information, the most important of whom were secret agents „Ares” and „Erski”. The operational methods used allowed Security Service offi cers to be familiar with moods among members of the editorial staff, comments about current events and some of the plans of the staff. Moreover, Security Service was well informed of the fi nancial situation of the magazine and was able to name all the magazine co-operators, also those who wanted to be anonymous and used pseudonyms. Among the defeats of the Security Service in the period described one can name the fact that its offi cers were not able to enrol for co-operation no-one from the main editors of the magazine. Another issue was that the Security Service did not know about plans of Jerzy Turowicz to sign so called „Letter of the 34” and was not able to prevent it.